2008
DOI: 10.1177/0022429408326762
|View full text |Cite
|
Sign up to set email alerts
|

A Discriminant Analysis of the Factors Associated With the Career Plans of String Music Educators

Abstract: The purpose of this study was to explore factors that may affect string teachers' career decisions. Six hundred string teachers were mailed a questionnaire designed to elicit responses about multiple factors and projected career plans in 1 year and in 5 years, and 304 teachers responded. The majority of teachers planned to remain in their positions the following year, whereas only half planned to remain in their positions in 5 years. Analyses indicated that work culture, perceptions about music's importance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Respondents also indicated that more opportunities for student collaborations were a benefit of the new string program. With more student collaborations, string music educators may also find ways of collaborating with other music educators in their building or district, which may lead to greater job satisfaction and career stability (Russell, 2008(Russell, , 2009. The majority of participants disagreed with most negative outcomes but reported some frustration with new scheduling difficulties and lack of performance facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents also indicated that more opportunities for student collaborations were a benefit of the new string program. With more student collaborations, string music educators may also find ways of collaborating with other music educators in their building or district, which may lead to greater job satisfaction and career stability (Russell, 2008(Russell, , 2009. The majority of participants disagreed with most negative outcomes but reported some frustration with new scheduling difficulties and lack of performance facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only 6% of respondents indicated a decrease in the district music budget, suggesting that new string programs did not strain the budgets of existing programs. Russell (2008) found that perceived support from several groups of stakeholders (i.e., other teachers, administrators, parents, and students) played a major role in the short-and long-term career plans of string music educators. Respondents in the current study identified an additional outcome of this support.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher intended this study to build upon previous research (Russell, 2008) but focus on a larger, yet specific, population of secondary (middle school and high school) ensemble directors whose positions may create conditions different than other music educators experience (e.g., large class sizes that impact their short-and long-term career plans). Moreover, current economic trends in the United States may also influence decisions to remain, find related employment, or leave teaching altogether.…”
mentioning
confidence: 99%
“…Conway and Holcomb 2008). As early career music teachers are at higher risk of attrition (Hancock 2008;Russell 2008) graduate programmes that offer authentic-context learning activities may be a way to combat unwanted teacher attrition through more meaningful graduate programmes. Participants in this study indicated that their authentic-context learning activities helped them develop commitment to teaching, improved confidence, as well as a teacher identity.…”
Section: Discussionmentioning
confidence: 99%